The structure of external labour migration from Ukraine in XXI century - Shabalina, Liudmyla; Vetrova, Svitlana (Skhid, 2013)
The article contains a review and analysis of the problems of external labour migration of Ukraine, in particular the structure of labour migration for period from 2000 to 2011. The factors of external labour migration influence on Ukraine’s development and it’s labour potential were qualitatively and quantitatively described.